The emerging role of MCPH1/BRIT1 in carcinogenesis - Alsolami, Mona; Aboalola, Doaa; Malibari, Dolal; Alghamdi, Tariq; Alshekhi, Walaa; Jad, Hind; Rumbold-Hall, Rea; Altowairqi, Ahlam S.; Bell, Sandra M.; Alsiary, Rawiah Abdullah (Frontiers in Oncology, 2023)
The MCPH1 gene, also known as BRCT-repeat inhibitor of hTERT expression (BRIT1), has three BRCA1 carboxyl-terminal domains which is an important regulator of DNA repair, cell cycle checkpoints and chromosome condensation. MCPH1/BRIT1 is also known as a tumour suppressor in different types of human cancer. The expression level of the MCPH1/BRIT1 gene is decreased at the DNA, RNA or protein level in a number of types of cancers including breast cancer, lung cancer, cervical cancer, prostate cancer and ovarian cancer compared to normal tissue. This review also showed that deregulation of MCPH1/BRIT1 is significantly associated with reduced overall survival in 57% (12/21) and relapsed free survival in 33% (7/21) of cancer types especially in oesophageal squamous cell carcinoma and renal clear cell carcinoma. A common finding of this study is that the loss of MCPH1/BRIT1 gene expression plays a key role in promoting genome instability and mutations supporting its function as a tumour suppressor gene.